Controlled synthesis of Ni3C/nitrogen-doped carbon nanoflakes for efficient oxygen evolution. (10th October 2019) - Hao, Jing; Zhang, Guofeng; Zheng, Yiteng; Luo, Wenhao; Jin, Cen; Wang, Ran; Wang, Zhen; Zheng, Wenjun
Abstract: Ni3 C is very promising in electrocatalytic field. However, it is rarely reported due to its harsh synthesis conditions. Herein, pure metallic Ni3 C nanoparticles in situ embedded in two-dimensional (2D) nitrogen-doped carbon nanoflakes (Ni3 C/NC nanoflakes) are successfully prepared through one-step pyrolyzing Ni-urea complex at a relatively mild temperature at 350 °C. The composition and nanostructure of the catalyst can be easily controlled by adjusting the synthetic conditions, such as pyrolysis temperature and reactant concentration. The NC nanoflakes with a large specific surface area and massive mesopores present a 2D morphology, which is beneficial to disperse Ni3 C nanoparticles to maintain their high conductivity. Based on advantage of nanostructure, Ni3 C/NC nanoflakes exhibit high electrocatalytic performance with a low overpotential of 309 mV, small Tafel slope of 72 mV dec −1, as well as good stability. Furthermore, this study could provide a new strategy for the design and fabrication of other transition-metal carbides.